2018
DOI: 10.1021/acs.nanolett.8b01912
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Hybrid Fano Resonances in Halide Perovskite Nanoparticles

Abstract: Halide perovskites are known to support excitons at room temperatures with high quantum yield of luminescence that make them attractive for all-dielectric resonant nanophotonics and meta-optics. Here we report the observation of broadly tunable Fano resonances in halide perovskite nanoparticles originating from the coupling of excitons to the Mie resonances excited in the nanoparticles. Signatures of the photon-exciton (" hybrid") Fano resonances are observed in dark-field spectra of isolated nanoparticles, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
121
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(124 citation statements)
references
References 43 publications
3
121
0
Order By: Relevance
“…Abujetas et al investigated theoretically light scattering from all‐dielectric nanorod, and found that the interference between Mie resonance and Fabry–Perot resonance leads to Fano resonance . Tiguntseva et al observed the photon‐exciton Fano resonance in the dark‐field spectrum of isolated halide perovskite nanoparticle . Moreover, Fano resonance has been demonstrated theoretically or experimentally in other individual all‐dielectric nanostructures such as Si split‐ring and Si core/shell nanoparticle .…”
Section: Introductionmentioning
confidence: 99%
“…Abujetas et al investigated theoretically light scattering from all‐dielectric nanorod, and found that the interference between Mie resonance and Fabry–Perot resonance leads to Fano resonance . Tiguntseva et al observed the photon‐exciton Fano resonance in the dark‐field spectrum of isolated halide perovskite nanoparticle . Moreover, Fano resonance has been demonstrated theoretically or experimentally in other individual all‐dielectric nanostructures such as Si split‐ring and Si core/shell nanoparticle .…”
Section: Introductionmentioning
confidence: 99%
“…Among them solution‐processed organic–inorganic perovskites have shown promising pathways in realizing tunable metasurfaces with their easy fabrication techniques and excellent photoresponsive properties . Further, solution processed perovskites have shown to exhibit plasmonic behavior and have emerged as novel platform for realizing tunable metasurfaces at optical frequencies . In the recent studies, it was shown that by photodoping the solution‐processed methyl ammonium lead iodide (CH 3 NH 3 PbI 3 ) perovskite materials spin coated on the metasurface aids in ultrasensitive reconfiguration of its resonances on rigid and flexible substrates at THz frequencies .…”
mentioning
confidence: 99%
“…can occur in gas phase when they are surrounded by an acid molecules (HI, HBr, or HCl). This approach was applied to resonant CsPbBr 3 nanoparticles as well and resulted in a broadband (∼1 eV) exciton spectral position tuning by applying HCl acid in gas phase by several minutes 95 . As shown in Fig.…”
Section: Structural and Active Coloringmentioning
confidence: 99%